2015
DOI: 10.1556/jfc-d-14-00029
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-Flow Hydroisomerization of C5–C7 Alkanes Using Mechanochemically Synthesized Supported Pt and Pd-SBA-15 Materials

Abstract: SBA-15 materials exhibit important properties including large surface area, highly ordered mesopores, and high stability in a variety of catalytic reactions. In this study, Al and Zr-loaded SBA-15 materials (Si/Zr = 30, Si/Al = 30), 50 molar ratio with Pd (1, 2, and 4% (w/w)) and Pt (0.5 and 1% (w/w)) were tested in the isomerization of C5-C7 linear alkanes. These solids were characterized using thermal gravimetric analysis-differential thermal analysis (TGA-DTA), nitrogen physisorption, and energy dispersive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Hidalgo et al studied the C 5 –C 7 alkane isomerization over Zr- and Al-loaded SBA-15 catalysts (SiO 2 /ZrO 2 = 30, and SiO 2 /Al 2 O 3 = 30) and 50 molar ratio of Pd (1, 2, and 4 wt %) and Pt (0.5 and 1 wt %). The results showed that Zr–SBA-15 catalysts were less active than Al–SBA-15.…”
Section: Isomerization Of C5–c6 Alkanesmentioning
confidence: 99%
“…Hidalgo et al studied the C 5 –C 7 alkane isomerization over Zr- and Al-loaded SBA-15 catalysts (SiO 2 /ZrO 2 = 30, and SiO 2 /Al 2 O 3 = 30) and 50 molar ratio of Pd (1, 2, and 4 wt %) and Pt (0.5 and 1 wt %). The results showed that Zr–SBA-15 catalysts were less active than Al–SBA-15.…”
Section: Isomerization Of C5–c6 Alkanesmentioning
confidence: 99%
“…Metal/acid bifunctional catalysts for alkane isomerization reactions have been studied extensively, such as Pt, Ni, and other metals loaded on molecular sieves. The metals provide hydrogenation and dehydrogenation active centers, while the molecular sieves supply acidic centers. The key to make this combination become an excellent catalyst to achieve the above goal is to balance the acidic and the metallic properties of the catalysts. …”
Section: Introductionmentioning
confidence: 99%